Bulgaria : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2000)
The paper assesses key aspects of Bulgaria's competitiveness. The challenge is to stay on course and persist with policies that will maintain and strengthen competitiveness. Implementation of the ambitious reform policy with respect to the pension and health care systems is required. The reasons for and implications of low bank credit to the private sector in Bulgaria, and measures to facilitate prudent credit growth are discussed. The statistical data on the economic indices of Bulgaria are also presented in the paper.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet